2017
DOI: 10.1002/met.1670
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic analysis of an intense rainfall event in Paraíba do Sul river basin in southeast Brazil

Abstract: ABSTRACT:The aim of this study was to analyse the characteristics of an intense rainfall event that occurred in the Paraíba do Sul river basin, southeast Brazil, in early 2000. Rainfall data from conventional meteorological stations and automatic weather stations, satellite images and datasets from the Climate Forecast System Reanalysis, National Centers for Environmental Prediction, were employed. After the arrival of a cold front in the state of São Paulo on 1 January, the first episode of the South Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
6
24
0
2
Order By: Relevance
“…During SACZOCN episodes the trough near Uruguay coast closes into a cyclonic vortex and moves northward, near the southeast coast of Brazil (compare Figure 4D with Figure 8C). Brasiliense et al (2018) named this closed cyclonic circulation as cyclonic vortex embedded in the SACZ (CVES). From Figures 8A,C it is clear that the CVES is not embedded in the SACZ, but southwest of it, near the RJ coast (see the location of RJ in Figure 5A).…”
Section: Oceanic Sacz Climatologymentioning
confidence: 99%
“…During SACZOCN episodes the trough near Uruguay coast closes into a cyclonic vortex and moves northward, near the southeast coast of Brazil (compare Figure 4D with Figure 8C). Brasiliense et al (2018) named this closed cyclonic circulation as cyclonic vortex embedded in the SACZ (CVES). From Figures 8A,C it is clear that the CVES is not embedded in the SACZ, but southwest of it, near the RJ coast (see the location of RJ in Figure 5A).…”
Section: Oceanic Sacz Climatologymentioning
confidence: 99%
“…Recent analysis presented by Brasiliense et al . associated a cyclonic vortex with subtropical characteristics to the occurrence of an extreme precipitation event over Paraíba do Sul river basin (in southeastern Brazil) occurring in January 2000.…”
Section: Subtropical Cyclones Over the Ocean Basismentioning
confidence: 99%
“…Recent analysis presented by Brasiliense et al 67 associated a cyclonic vortex with subtropical characteristics to the occurrence of an extreme precipitation event over Paraíba do Sul river basin (in southeastern Brazil) occurring in January 2000. For this event, Sugahara et al 68 classified the observed accumulated rainfall during 5 days (which in one rain gauge station reached up to 522 mm) as an extremely rare event for the region, that is, with probability of occurrence less than 1% for most rain gauge stations.…”
Section: And Evans Andmentioning
confidence: 99%
“…A recent study by Brasiliense et al () analysed an intense cyclone near the southeastern coast of Brazil in January 2000 and the SLP analysis presented in their study resembles the field given in Figure c, except that the central closed isobar value in their case was 1,006 hPa. In the present study the field shown is the composite of 80 cases and therefore the cyclone is less intense.…”
Section: Resultsmentioning
confidence: 79%
“…The cyclogeneses over these small areas are focused because they impart precipitation and weather changes to adjacent coastal regions. One example of a cyclone development which imparted excessive precipitation in the coastal regions of southeastern Brazil is presented by Brasiliense et al ().…”
Section: Methodsmentioning
confidence: 99%